The Protein Scaffold NHERF-1 Controls the Amplitude and Duration of Localized Protein Kinase D Activity - Kunkel, Maya T.; Garcia, Erin L.; Kajimoto, Taketoshi; Hall, Randy A.; Newton, Alexandra C. (The Journal of biological chemistry, 2009)
Protein kinase D (PKD) transduces an abundance of signals downstream of diacylglycerol production. The mammalian PKD family consists of three isoforms, PKD1, PKD2, and PKD3; of these PKD1 and PKD2 contain PDZ-binding motifs at their carboxyl termini. Here we show that membrane-localized NHERF scaffold proteins provide a nexus for tightly controlled PKD signaling via a PDZ domain interaction. Using a proteomic array containing 96 purified PDZ domains, we have identified the first PDZ domain of NHERF-1 as an interaction partner for the PDZ-binding motifs of both PKD1 and PKD2. A fluorescence resonance energy transfer-based translocation assay reveals a transient association of PKD1 and PKD2 with NHERF-1 in live cells that is triggered by phorbol ester stimulation and, importantly, differs strikingly from the sustained translocation to plasma membrane. Targeting a fluorescence resonance energy transfer-based kinase activity reporter for PKD to NHERF scaffolds reveals a unique signature of PKD activation at the scaffold that is distinct from that of general cytosolic or plasma membrane activity. Specifically, agonist-evoked activation of PKD at the scaffold is rapid and sustained but blunted in magnitude when compared with cytosolic PKD. Thus, live cell imaging of PKD activity demonstrates ultrasensitive control of kinase signaling at the scaffold compared with bulk activity in the cytosol or at the plasma membrane.